Screening, diagnosing and treating deafness – the knowledge and conduct of doctors serving in neonatology and/or pediatrics in a tertiary teaching hospital - Colozza, Patrícia; Anastasio, Adriana Ribeiro Tavares (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Infant hearing deficiency is a human disorder with devastating effects and serious implications for the development of speech and language. Early diagnosis of hearing loss should be the objective of a multidisciplinary team, and early-intervention programs should immediately follow this. The aim of this study was to investigate the knowledge and conduct of pediatricians and pediatric residents in a tertiary teaching hospital regarding deafness. DESIGN AND SETTING: Cross-sectional study in a tertiary hospital in the state of São Paulo, Brazil. METHODS: Eighty-eight questionnaires were randomly distributed to pediatricians and pediatric residents. RESULTS: Thirty-six questionnaires were analyzed. Most respondents (61.1%) were residents in pediatrics and/or neonatology. Eighty-three percent of them performed special procedures on babies presenting a high risk of deafness, and 55% reported that they had no knowledge of techniques for screening hearing. Most of them were unaware of the classifications of level and type of hearing loss. According to 47.2% of them, infants could begin to use a hearing aid at six months of age. Most of them reported that infants could undergo hearing rehabilitation during the first six months of life, and all respondents stated that being concerned about child communication is part of a doctor’s responsibilities. CONCLUSIONS: Even though most of the participants followed special procedures with babies presenting a high risk of deafness, they did not routinely investigate hearing. All respondents believed that it is a doctor’s responsibility to be concerned about child communication.